Drip Irrigation: The BMP Era - An Integrated Approach to Water and Fertilizer Management for Vegetables Grown with Plasticulture - Eric Simonne; David Sudstill; Bob Hochmuth; Teresa Olczyk; Michael Dukes; Rafael Munoz-Carpena; Yuncong Li (EDIS)
This article presents a summary of the information discussed on fertilizer management, irrigation scheduling, and drip system maintenance and troubleshooting. A list of additional references is also included. This document is HS917, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 2003.